Non-Formal Education Management for The Residents of The Rejang Lebong Development Institution - Murni Yanto (Nazhruna: Jurnal Pendidikan Islam, 2022)
In The Class IIA Correctional Institution Rejang Lebong in giving directions to prisoners, it provides non-formal training administration as a Package C equivalency school. In offering this instructive assistance, good administration is expected to achieve quality instructive goals. Objectives of exploration: (1) implementation of non-formal instruction program at Rejang Lebong Penitentiary, (2) obstacles faced, and efforts to conquer obstacles in Lapas Rejang Lebong. This kind of examination is a subjective exploration of graphics. Procedures vary information based on perceptions, meetings, and documentation. The results showed that the implementation of a non-formal instruction program for prisoners completed by the penitentiary had gone very well, despite the fact that it actually faced many obstacles. Prison helps PKBM "Bina Sejahtera" which is under the control of the Ministry of Education and Culture.